Kemampuan Pemecahan Masalah Kontekstual Siswa SMA Kelas XI pada Materi Barisan dan Deret - Astuti, Puji; Sari, Nina Kurniati; Wirawan, Fajar (ANTHOR: Education and Learning Journal, 2023)
This article is a study that aims to describe the ability to solve contextual problems of class IXhigh school students on the basis of material and series. Problem solving is a very important part of learning mathematics because in the process of learning and solving math problems, it is possible for students to gain experience using the knowledge they already have. One of the problem solving methods used is according to Polya. There are four initial steps to solving a problem according to Polia, namely understanding the problem, making a problem solving plan, carrying out a settlement plan and re-examining the results of the settlement. Based on this, a study was conducted which aimed to determine the development of students' problemsolving abilities and to find out whether there were significant differences in student learning outcomes between before and after being given the problem-solving method according to Polya. The results obtained in this study were that students were able to understand the problem from the questions and get the answers correctly but in compiling and implementing student plans it was not appropriate when using the stages from Polya.